The IGF/IGFBP system in relation to macroscopic bone architecture in pediatric renal transplant patients - Choukair, Daniela; Rüth, Eva-Maria; Blum, Werner F.; Mohan, Subburaman; Weber, Lutz T.; Tönshoff, Burkhard (Pediatric nephrology, 2010)
The post-transplant bone disease of the peripheral skeleton in pediatric renal transplant recipients is characterized by an inadequately thin bone cortex in relation to muscular force. A major hormonal modulator of periosteal growth is the insulin-like growth factor (IGF)/IGF binding protein (IGFBP) system. We therefore hypothesized that the reduced cortical thickness in these patients may be due to functional IGF deficiency.